Truth and Politics. A Vulnerable Realm - Fantauzzi, Stefania (HannahArendt.net, 2021)
The objective of this article is to discuss some aspects of Hannah Arendt’s thought on the relationship between truth and politics, which, although they were developed in a different context from the current one, are particularly relevant to reflecting on the notion of the “fake,” a concept which has become such a characteristic feature of contemporary culture that it is now a way of structuring our model of reality. Arendt’s contribution is analysed following two basic lines of argument. Firstly, we seek to show that her ideas reveal the problem of truth as it currently emerges to be one of indifference towards reality and the world. Subsequently we explain how this indifference relates to another key point in Arendt’s thought, namely, responsibility towards this same world. Once the synergy between responsibility and the world has been established, we examine the roles of the narrator and the spectator in constructing the relationship between truth and lies.